Health professional students' rural placement satisfaction and rural practice intentions: A national cross‐sectional survey. (16th August 2017) - Smith, Tony; Sutton, Keith; Pit, Sabrina; Muyambi, Kuda; Terry, Daniel; Farthing, Annie; Courtney, Claire; Cross, Merylin
Abstract: Objective: The aim of this study was to profile students undertaking placements at University Departments of Rural Health (UDRHs) and investigate factors affecting students' satisfaction and intention to enter rural practice. Design: Cross‐sectional survey comprising 21 core questions used by all UDRHs. Setting: Eleven UDRHs across Australia that support students' placements in regional, rural and remote locations. Participants: Medical, nursing and allied health students who participated in UDRH placements between July 2014 and November 2015 and completed the questionnaire. Main outcome measures: Key dependent variables were placement satisfaction and rural practice intention. Descriptive variables were age, gender, Aboriginal or Torres Strait Islander (ATSI) background, location of placement, healthcare discipline, year of study and type and length of placement. Results: A total of 3328 students responded. The sample was predominantly female (79%), the mean age was 26.0 years and 1.8% identified as ATSI. Most placements (69%) were >2 but ≤12 weeks, 80% were in Modified Monash 3, 4 or 5 geographical locations. Public hospitals and community health made up 63% of placements. Students satisfied with their placement had 2.33 higher odds of rural practice intention. Those satisfied with Indigenous cultural training, workplace supervision, access to education resources and accommodation had higher odds of overall satisfaction and post‐placement rural practice intention. Conclusions: The majority of students were highly satisfied with their placement and the support provided by rural clinicians and the UDRHs. UDRHs are well placed to provide health professional students with highly satisfactory placements that foster rural practice intention.